2014
DOI: 10.1002/jbio.201400007
|View full text |Cite
|
Sign up to set email alerts
|

Combined antibacterial effects of tissue‐tolerable plasma and a modern conventional liquid antiseptic on chronic wound treatment

Abstract: Potential antimicrobial effects of sequential applications of tissue-tolerable plasma (TTP) and the conventional liquid antiseptic octenidine dihydrochloride (ODC) were investigated. 34 patients with chronic leg ulcers were treated with TTP, ODC or a combination of both. The bacterial colonization was measured semi-quantitatively before and immediately after treatment and changes in the microbial strains' compositions before and after antiseptic treatments were analyzed. All antiseptic procedures reduced the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 23 publications
(37 reference statements)
2
30
1
Order By: Relevance
“…This three‐arm RCT reported that the application of AP or OCT result in similar “microbial reduction classes,” with no further reduction if both treatments were applied sequentially on wounds. At first glance, the finding of Klebes et al appears to be in direct contrast to the results reported by Ulrich et al However, both RCTs used absolutely not comparable microbiological measurements. Because of this and other limitations, we therefore could not include this latter RCT into our meta‐analysis as, in most of the 34 included patients, the three treatment procedures were performed on each wound, and only the immediate antibacterial effect of the applied interventions were investigated and reported semi‐quantitatively as “4—abundant,” “3—moderate growth,” “2—little growth,” “1—marginal growth,” and “0—no growth.” Finally, changes of wound size and occurrence of SAEs were not included as outcome measures in this study …”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This three‐arm RCT reported that the application of AP or OCT result in similar “microbial reduction classes,” with no further reduction if both treatments were applied sequentially on wounds. At first glance, the finding of Klebes et al appears to be in direct contrast to the results reported by Ulrich et al However, both RCTs used absolutely not comparable microbiological measurements. Because of this and other limitations, we therefore could not include this latter RCT into our meta‐analysis as, in most of the 34 included patients, the three treatment procedures were performed on each wound, and only the immediate antibacterial effect of the applied interventions were investigated and reported semi‐quantitatively as “4—abundant,” “3—moderate growth,” “2—little growth,” “1—marginal growth,” and “0—no growth.” Finally, changes of wound size and occurrence of SAEs were not included as outcome measures in this study …”
Section: Discussioncontrasting
confidence: 56%
“…To our knowledge, there is only one more RCT that compared AP against OCT or the sequential application of AP followed by OCT treatment on chronic, open wounds . This three‐arm RCT reported that the application of AP or OCT result in similar “microbial reduction classes,” with no further reduction if both treatments were applied sequentially on wounds.…”
Section: Discussionmentioning
confidence: 99%
“…In this field called plasma medicine, encouraging results have been achieved for disinfection purposes [2], in vitro [3,4,5] and in patients [6,7,8]. Notably, a key feature determining healing is the state of wound oxygenation [9], and evidence suggests that the scavenging of active oxygen species impairs wound healing [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that CAP treatment influences gene expression of key regulators that are important for inflammation and wound healing, as well as activation of antimicrobial peptides [16]. CAP has been clearly shown to enhance the wound healing effect when used in combination with certain antiseptic liquids [17]. Therefore, CAP is currently in use as a decontaminant in hospital environments [18] and for functionalization of wound dressings [19].…”
mentioning
confidence: 99%